(untitled) (Simbiótica. Revista Eletrônica, 2024)
The Statute for victims of crime, approved by Law 4/2015, of April 27, recognizes procedural and extra-procedural rights for all victims. Among others, the right to access support services through the Crime Victim Assistance Offices stands out, due to their special contribution to the de-victimization process. Through a socio-legal study, it is reported the possibilities that victims of violence in same-sex couples must resort to this resource, but also the limits that the implementation of this right entails in the face of this violence. This research indicates suggestions for future research to improve care and support for victims.